Description of Physical Activity and The Incidence of Type 2 Diabetes Mellitus in Pringapus Hamlet, Temanggung District - Cahyo Wibowo; Venti Agustina; Antok Widya Nugroho (Journal Physical Education, Health and Recreation, 2021)
Type 2 diabetes mellitus is a disease characterized by hyperglycemia and metabolic disorders caused by a relative lack of carbohydrates, proteins, and fats. The research was conducted to know the description of physical activity and the incidence of type 2 diabetes mellitus in Pringapus Hamlet. The type of research used is descriptive quantitative with a male population of 30 respondents between the ages of 17-25 years consisting of 11 teenagers and 19 adults. The results showed that the majority of respondents had low activity as many as 23 (76.6%) respondents, while in type 2 diabetes mellitus the results of blood sugar examinations with 30 respondents were in the normal blood sugar category (GDS < 200 mg/dL), and based on the results calculation of body mass index found 1 respondent (3.3%) with obese nutritional status and 2 respondents (6.6%) with obese nutritional status. From the results of research conducted by researchers, it can be concluded that the majority of respondents have low activity levels, namely 23 (76.6%) respondents, while for the incidence of type 2 diabetes mellitus, based on the results of blood sugar examinations, all respondents (30 respondents) entered the blood sugar category. normal (GDS < 200 mg/dL).